Emotional abuse and its relationship to academic achievement among primary school pupils - محمد حسن العبيدي, بشرى (Al-Adab Journal, 2018)
The current study sought to identify the emotional abuse among pupils and their relationship to academic achievement at the elementary level, where is the problem of child neglect and abuse him one of the most serious social problems that stand in the face of the progress of society and its development, and that affect the mental and emotional health of the pupil, causing him harm or serious harm affects the manifestations of psychological negative effects continue to improve through the rest of the stages of life, making them suffer from a wide range of psychological and behavioral disorders in turn affect the academic achievement of students, where the study aimed to .Used where the researcher research methodology descriptive sample consists of 80 pupils, was chosen the way intentionality and according attainment variable, and the rate of (40) pupils are superior, and (40) pupils is superior, for grades fifth and sixth primary, aged (10 -14 years), where the search results showed that there are differences statistically significant differences in emotional abuse variable and academic achievement among students excelling (males, females) and non-talented (male, female), and that there are differences between pupils gifted and non-gifted, while there are no differences between students excelling and is excelling male, and that there is a negative relationship statistically significant in emotional abuse variable and academic achievement. Any greater the emotional abuse Say attainment, and lower the abuse increased academic achievement .astkhaddmt the researcher test samples t (T-test (for two independent samples, and transactions Pearson correlation to identify the nature of the relationship between Almngaran.thm researcher recommended the need to educate the family and community organizations concerned with the welfare of the child such as school quality and educational tactics to deal with the student, and the awareness of the media about the negative effects of the abuse emotional on the student, and activating the role of religious institutions to combat violence and abuse against children.